Indonesia’s Climate Change Policies: Under the Tug of Domestic and International Influences - Isnaini, Dani Mochtar (JURNAL ILMU SOSIAL, 2021)
Paris Agreement with its ‘bottom-up’ approach is an attempt to address climate change problem. The Parties of the Paris Agreement decide their own policies in the national scope and present it as pledges in the form of Nationally Determined Contributions (NDCs). I explore the evidence to the shaping of the climate change policies in Indonesia, mainly regarding NDCs and the engagement of actors behind the shaping of that pledge. The main question is which actor or combination of actors in terms of domestic and international interests actually influenced and shaped Indonesia’s NDCs? This article aims to give practical evidence regarding the influences of different positions among competing interests through negotiation. In terms of Indonesia’s policymaking, this study is hoped to foster a viewpoint for the sake of acceptable practices to intensify policymaking preferences. In this literature review Liberal Intergovernmentalism propositions were used in examining the dynamics at the domestic level as well as transnational/regional negotiation and interdependence. I also used multiple sources from other studies and governmental documents in the analysis of this qualitative research. As a result, some evidence were found, showing the influence of domestic actors such as Local and Environmental NGOs, CSOs, public perceptions to certain extent, and insignificant influence of business groups. I also found that the transnational institutions and developed countries have impacts on Indonesia’s CC policy framework, funding provision and the balance between mitigation and adaptation.